Achilles tendon compositional and structural properties are altered after unloading by botox. Issue 1 (December 2017) - Khayyeri, Hanifeh; Blomgran, Parmis; Hammerman, Malin; Turunen, Mikael; Löwgren, Annika; Guizar-Sicairos, Manuel; Aspenberg, Per; Isaksson, Hanna
Abstract Tendon function and homeostasis rely on external loading. This study investigates the biological mechanisms behind tendon biomechanical function and how the mechanical performance is affected by reduced daily loading. The Achilles tendons of 16 weeks old female Sprague Dawley rats (n = 40) were unloaded for 5 weeks by inducing muscle paralysis with botulinum toxin injections in the right gastrocnemius and soleus muscles. The contralateral side was used as control. After harvest, the tendons underwent biomechanical testing to assess viscoelasticity (n = 30 rats) and small angle X-ray scattering to determine the structural properties of the collagen fibrils (n = 10 rats). Fourier transform infrared spectroscopy and histological staining (n = 10 rats) were performed to investigate the collagen and proteoglycan content. The results show that the stiffness increased in unloaded tendons, together with an increased collagen content. Creep and axial alignment of the collagen fibers were reduced. Stress-relaxation increased whereas hysteresis was reduced in response to unloading with botox treatment. Our findings indicate that altered matrix deposition relies on mechanical loading to reorganize the newly formed tissue, without which the viscoelastic behavior is impaired. The results demonstrate that reduced daily loading deprives tendons of their viscoelastic properties, which could increase the risk of injury.